EXIT Llyod Davies - Mohd Faizal A.,; Vijayan V.,; Sandhya MM.,; Noor Shahieddah F.,; Vinod S.,; Tan, LK.; Soon R., (Department of Surgery, UKM Medical Centre, 2015)
The EXIT (Ex utero intrapartum treatment) procedures have been, with a high degree of success, employed to treat a myriad types of fetal airway obstruction most commonly neck masses such as cystic hygroma and lymphangioma with ample plan including prenatal diagnosis by ultrasound scan or MRI. Before the advent of EXIT, formal documentations had been published with descriptions of intubation during intrapartum period and fetal airway protection either during normal or operative delivery. We report a 28-year-old gravida 2 para 1 who was referred to our Maternal Fetal Medicine (MFM) unit at 26 weeks and 3 days gestation with a foetal neck mass. We present a case of an successful EXIT procedure performed in the Lloyd Davies position with the hips abducted and flexed at 15 degrees as is employed during gynecologic laparoscopy surgery minus the Trendelenburg tilt. Both mother and baby are well. The benefits of this position are discussed.